Organic synthesis of 1,2-O-Isopropylidene-3-acyl glycerol by Amberlite XAD-7 adsorbed lipase of Pseudomonas sp. AK - Lo, Ya Sien; Omar, Ibrahim Che (Penerbit Universiti Sains Malaysia, 2004)
Monoacylglycerols (MG) are widely used as emulsifiers mainly in the food, cosmetics and pharmaceutical industries. MG can be chemically synthesized via glycerolysis or hydrolysis of fats and oils at high temperature using inorganic catalysts. Chemical synthesis through esterification of 1,2-0-isopropylidene glycerol with acid chloride, followed by subsequent hydrolysis of the ketal has also been reported (Quinn et al., 1967).